1996
DOI: 10.1080/026990596124386
|View full text |Cite
|
Sign up to set email alerts
|

Chronic elemental mercury intoxication: neuropsychological follow-up case study

Abstract: In initial and follow-up investigations of neuropsychological function in a patient with elemental mercury intoxication, his scores were compared with those of a group of normal control subjects matched for sex, age and education. Each subject received a comprehensive neuropsychological examination including a personality inventory. On the initial examination the results indicated that the patient had a significant depression of performance intellectual functioning, impairments of attention, non-verbal short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
11
0
3
Order By: Relevance
“…Lithium protects brain cells against excess glutamate and calcium (Rossi et al 1993;Nonaka et al 1998). Mercury inhibits macrophage and neutrophil defense against candida by affecting Th1 and Th2 cytokine effects (Perlingeiro and Queiroz 1994;Mathieson 1995;Hua et al 1996). Candida overgrowth results in production of the highly toxic canditoxin and ethanol which are known to cause fatigue, toxicity, and depressive symptoms (Crook 1984;Edwards 1985).…”
Section: Electrolytes and Trace Metalsmentioning
confidence: 99%
“…Lithium protects brain cells against excess glutamate and calcium (Rossi et al 1993;Nonaka et al 1998). Mercury inhibits macrophage and neutrophil defense against candida by affecting Th1 and Th2 cytokine effects (Perlingeiro and Queiroz 1994;Mathieson 1995;Hua et al 1996). Candida overgrowth results in production of the highly toxic canditoxin and ethanol which are known to cause fatigue, toxicity, and depressive symptoms (Crook 1984;Edwards 1985).…”
Section: Electrolytes and Trace Metalsmentioning
confidence: 99%
“…It is a central nervous system syndrome (9) involving sensory losses that affect visual function (10)(11)(12), emotional disturbances (13) and personality changes including irritability, agitation, mood lability, shyness, and depression (5,8,(14)(15)(16). Symptoms of mercurialism can be found in individuals with a history of chronic exposure to mercury vapor years after the exposure has ceased.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies with industry workers currently exposed to mercury vapor have found deficits in shortterm memory (17,18), mental arithmetic, switching attention, and reaction time (19), psychomotor function (19,20), logic memory, and manual dexterity (21). However, not all studies find changes in the same parameters (13,22,23) and this disagreement could not be explained by the exposure levels (23). Among the effects of mercury intoxication, motor impairment is apparently the most consistently reported symptom (9,23).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies in occupationally exposed adults suggest that the effects of adult mercury poisoning are reversible with treatment (25). However, extensive studies of the chronic effects of lower level metallic mercury poisoning have not been undertaken in adults, and even less research has been done in children.…”
Section: Discussionmentioning
confidence: 99%